KERAGAMAN BAKTERI ASAM LAKTAT SECARA MOLEKULER PADA ILEUM DAN SEKUM AYAM BROILER YANG DIBERI PAKAN PREBIOTIK BEKATUL DAN BEKATUL HASIL FERMENTASI - Laelatul Baniyah; Siti Nur Jannah; MG Isworo Rukmi (Jurnal Akademika Biologi, 2017)
Lactic Acid Bacteria (LAB) is a digestive tract microflora that play a positive role in poultry health. The number and diversity of LAB in the digestive tract affected by several factors, among them was the kind of feed. The purpose of this research was  to know the molecular diversity of Lactic Acid Bacteria (LAB) in broiler’s ileum and cecum  after  feeding with  prebiotic bran and Rhizopus oryzae fermented  bran which was added to commercial feed. The molecular analysis was done using T-RFLP method , Hae III and Msp I were used as restriction enzymes.  The number of phylotype, relative abundance, Shannon diversity index (H '), evenness (E), and Dominance (D)  were examined . The results indicated that the addition of bran prebiotics on commercial feed showed a higher  diversity of lactic acid bacteria on broiler’s ileum and cecum, compared  with the addition of Rhizopus oryzae fermented  bran. The dominant BAL types are Lactobacillus spp, L. delbrueckii subs. Bulgaricus, L. intermedius, L. amilovorus, uncultured bacteria 87 bp, 280 bp, 331 bp and unidentified bacteria 74 bp, 82 bp, 131 bp. Keywords: Diversity, Lactic Acid Bacteria, Prebiotics, Bran, T-RFLP